The Agenda 2030. The commitments derived from the objectives of a sustainable development in Mexico and in the world, the climate change, the challenges and the waste theme (Rivista di Studi e Ricerche sulla criminalità organizzata, 2019)
The environmental and social challenges facing humanity in the 21st century force a deep and integral reflection on the challenges of sustainable development. Thus, the 2030 Agenda sets sustainable development goals for the international community. Mexico assumes a State commitment to these objectives, so it is necessary to verify compliance with measurements that reflect positive qualitative changes at the federal, state and municipal levels.Keywords: Sustainable development, citizen audits, waste management, health risks, organized crime, corruption, money laundering prevention, international cooperation, technological innovation, culture of peace
Keywords: Sustainable development, citizen audits, waste management, health risks, organized crime, corruption, money laundering prevention, international cooperation, technological innovation, culture of peace